Accidental displacement of impacted maxillarythird molar: A case report - Mohammed Zuhaib; Pradeep Sharma; Bonita Doley (International Journal of Medical Research and Review, 2015)
An unusual case of an impacted right maxillary third molar that was accidentally displaced into the maxillary sinus during exodontia was surgically retrieved almost 2 months later is described. The tooth was removed under Local anesthesia, after maxillary sinus exposure through Caldwell-Luc approach. Postoperative recovery was uneventful. A month after the retrieval surgery, the maxillary sinus was fully healed and the patient did not present with any complaint.